Eine neue Rolle für die Europäische Zentralbank? Anmerkungen zu einem spezifisch Deutschen Konflikt. A new role for the European Central Bank? Remarks on a special German conflict - Ehrig, Detlev (Estonian Discussions on Economic Policy, 2016)
The recent European debt crisis has generated a growing importance of the ECB. The central bank was forced to take measures far beyond its traditional role to stabilize monetary markets and inflation. The European central bank has adopted a new function as lender of last resort, providing banks and governments with almost unlimited liquidity. The new and unconventional monetary policy has been hotly debated. In Germany the debate even reached the Constitutional Court. The article will give a survey of the debate referring to the arguments of the ECB versus Deutsche Bundesbank. It is indeed questionable whether the ECB has a mandate for its new role in monetary and by the way also fiscal policy. Whatever the arguments are convincing, new steps towards fiscal arrangements and a deeper political cooperation are needed to stabilize the euro area.